Ethnomathematics of Kalimantan Batik in field Geometry learning in elementary school - Sudrajat, Sudrajat; Winarto, Andi; Wicaksono, Bintang (SAINTIS Publishing, 2023)
This article examines the use of ethnomathematics in Kalimantan batik in learning geometry in elementary schools. The purpose of this paper is to explore mathematical concepts contained in the Kalimantan batik motifs that can be utilized in the process of learning geometry in elementary schools. This research uses exploratory research and an ethnographic approach. The research data were obtained from literature studies, observations, interviews, and documentation. Based on the results of the study this study obtained 6 types of Kalimantan batik motifs, namely Tidayu batik motif (West Kalimantan), spot yarn motif (Central Kalimantan), Empiek Batik motif (East Kalimantan), clouded motif batik motif (West Kalimantan), Sasirangan batik motif Hiris Pudak (South Kalimantan), Pating Muang batik motif (Central Kalimantan). Geometry concepts for elementary school children in Kalimantan batik motifs are rectangles, circles, triangles, points, lines, minimum and maximum curves, reflection, translation, and fraction numbers. The alternative steps of learning are as follows: (1). Students and teachers carry out learning with the question and answer methods related to Kalimantan batik motifs; (2). Students are asked to observe the Kalimantan batik motif; (3). Students are asked to analyze the shapes contained in the Kalimantan batik motif; (4) Students are asked to present their work.